Perbandingan Hasil Belajar Menggunakan Model Pembelajaran Numbered Head Together dengan Talking Stick Pelajaran Sejarah - Siti Rohmatun Nasikha; Muhammad Basri; Suparman Arif (FKIP UNIVERSITAS LAMPUNG, 2019)
The purpose of this study was to find out the student learning outcomes by using between Numbered Head Together (NHT) or Talking Stick learning model’s in the XI Social Sciences Historical subjects in Bangunrejo 1 Senior High School 2017/2018 school year. The research method used was comparative method with experiment approach method. The results of data analysis showed that students learning outcomes who learn using Numbered Head Together (NHT) learning model were better than student who learned using Talking Stick learning model in the XI Social Sciences Historical subjectsin Bangunrejo 1 Senior High School 2017/2018 school year.Tujuan penelitian ini untuk mengetahui lebih baik hasil belajarsiswa dengan menggunakan model pembelajaran Numbered Head Together (NHT) atau model pembelajaran Talking Stick pada Mata Pelajaran Sejarah Kelas XI IPS SMA Negeri 1 Bangunrejo Tahun Ajaran 2017/2018. Metode penelitian yang digunakan adalah metode komparataif dengan pendekatan eksperimen. Hasil analisis data menunjukan bahwa hasil belajar siswa yang belajar menggunakan model pembelajaran Numbered Head Together (NHT) lebih baik dari pada menggunakan model pembelajaran Talking Stick pada Mata Pelajaran Sejarah Kelas XI IPS SMA Negeri 1 Bangunrejo Tahun Ajaran 2017/2018.Kata kunci: numbered head together, perbandingan, talking stick